Impact of COVID-19 Infection Among Heart Transplant Recipients: A Southern Brazilian Experience - Scolari, Fernando Luis; Hastenteufel, Laura Caroline Tavares; Einsfeld, Lídia; Bueno, Julia; Orlandin, Letícia; Clausell, Nadine; Goldraich, Lívia Adams (Frontiers in Medicine, 2022)
Purpose: The coronavirus-2019 (COVID-19) infection is associated with a high risk of complications and death among heart transplant recipients. However, most data are described in high-income countries and data there is a paucity of data from Latin America. Methods: This is a retrospective cohort of heart transplant recipients followed at a hospital in Rio Grande do Sul, Brazil, between March 1st 2020 to October 1st 2021. Results: From 62 heart transplant recipients on follow-up, 21 (34%) were infected by COVID-19, with 58 (36-63) years of age, 67% male, body mass index of 26 (23-29) kg/m², 48% with hypertension, 43% with chronic kidney disease, 5% with diabetes, within 2 (1-4) years of post-transplant follow-up. At presentation, main symptoms were fever (62%), myalgia (33%), cough (33%), headache (33%), and dyspnea (19%). Hospitalization was required for 13 (62%) patients, with a time from first symptoms to admission of 5 (1-12) days. In 38%, supplementary oxygen was needed, 19% required intensive care, and 10% mechanical ventilation. Three (14%) were infected after at least a first dose of COVID-19 vaccine. Main complications were bacterial pneumonia (38%), renal replacement therapy (19%), sepsis (10%) and venous thromboembolism (10%). Immunosuppression therapy was modified in 48%, with reduction in the majority (89%). Two (10%) patients died in hospital due to refractory hypoxemia and multiple organ dysfunction. The prevalence of COVID-19 among transplant patients was comparable to the general population in the State of Rio Grande do Sul with a peak in December 2020. Conclusion: Heart transplant recipients had a high rate of COVID-19 infection in Southern Brazil, with typical symptom presentation in most cases. There was an elevated rate of hospitalization, supplementary oxygen support, and complications. In-hospital mortality among infected heart transplanted recipients was similar to previously reported data worldwide despite the high rates of infection in Latin America.